Mobility restriction and barrier-reduced housing among people aged 65 or older in Germany: Do those who need it live in barrier-reduced residences? - Nowossadeck, Sonja; Romeu Gordo, Laura; Lozano Alcántara, Alberto (Frontiers in Public Health, 2023)
Introduction Older people spend a lot of time at home and in the area near where they live. Housing conditions ensure their ability to participate in social life, especially when they suffer from mobility restrictions. Barrier-free access to the residence and to rooms within the residence is a key condition for their everyday mobility. As a result, this is what we define as minimal criteria for barrier-reduced residences. This article examines the extent to which people aged 65 and over (including people with mobility issues) live in barrier-reduced housing and what factors influence the chance of living in such residences. Data and method Cross-sectional data from the German Ageing Survey (DEAS) 2020/21 (persons aged 65 and over, n = 2,854) were used. The DEAS is a representative cross-sectional and longitudinal survey of the population aged 40 and over in Germany. In our analyses, we used logistic regression models to investigate the probability of living in a barrier-reduced residence. We defined housing as barrier-reduced when the apartment/house and the rooms inside it can be reached without steps or stairs. As explanatory variable, we considered mobility restrictions, defined as limited ability to climb a flight of stairs. In addition, the model includes other individual factors (age, gender, equivalized household income), regional factors (living in East vs. West Germany, in urban vs. rural region) and moving to the current residence after the age of 65. Results and discussion Of all individuals aged 65 or older, 19.3 percent live in a barrier-reduced residence. Also, of mobility-restricted elders, only 21.4 percent have such residences. The logistic regression results show that mobility restrictions are associated with a higher probability of living in a barrier-reduced residence. Compared to the lowest income group, older people in the highest income group are more likely to live in barrier-reduced housing. East Germans and people in urban areas are less likely to live in a barrier-reduced home. The likelihood of barrier-reduced living is higher among seniors who moved into their current residence after age 65. No significant differences were found for age groups and gender. The findings show that not enough seniors have barrier-reduced access to their homes and rooms, even if they suffer from mobility restrictions. Preventing functional restrictions must therefore also include improvements in the residential environment, especially in disadvantaged residential areas.